Magnetically separable and reusable rGO/Fe3O4 nanocomposites for the selective liquid phase oxidation of cyclohexene to 1, 2-cyclohexane diol. Issue 56 (11th October 2019) - Pudukudy, Manoj; Jia, Qingming; Dong, Yanan; Yue, Zhongxiao; Shan, Shaoyun
Abstract : A series of magnetically-separable and reusable rGO/Fe3 O4 nanocomposites were successfully synthesized for the selective liquid-phase oxidation of cyclohexene to 1, 2-cyclohexane-diol. Abstract : A series of magnetically separable rGO/Fe3 O4 nanocomposites with various amounts of graphene oxide were successfully prepared by a simple ultrasonication assisted precipitation combined with a solvothermal method and their catalytic activity was evaluated for the selective liquid phase oxidation of cyclohexene using hydrogen peroxide as a green oxidant. The prepared materials were characterized using XRD, FTIR, FESEM, TEM, HRTEM, BET/BJH, XPS and VSM analysis. The presence of well crystallized Fe3 O4 as the active iron species was seen in the crystal studies of the nanocomposites. The electron microscopy analysis indicated the fine surface dispersion of spherical Fe3 O4 nanoparticles on the thin surface layers of partially-reduced graphene oxide (rGO) nanosheets. The decoration of Fe3 O4 nanospheres on thin rGO layers was clearly observable in all of the nanocomposites. The XPS analysis was performed to evaluate the chemical states of the elements present in the samples. The surface area of the nanocomposites was increased significantly by increasing the amount of GO and the pore structures were effectively tuned by the amount of rGO in the nanocomposites. The magnetic saturation values of the nanocomposites were found to be sufficient for their efficient magnetic separation. The catalytic activity results show that the cyclohexene conversion reached 75.3% with a highest 1, 2-cyclohexane diol selectivity of 81% over 5% rGO incorporated nanocomposite using H2 O2 as the oxidant and acetonitrile as the solvent at 70 °C for 6 h. The reaction conditions were further optimized by changing the variables and a possible reaction mechanism was proposed. The enhanced catalytic activity of the nanocomposites for cyclohexene oxidation could be attributed to the fast accomplishment of the Fe 2+ /Fe 3+ redox cycle in the composites due the sacrificial role of rGO and its synergistic effect with Fe3 O4, originating from the conjugated network of π-electrons in its surface structure. The rapid and easy separation of the magnetic nanocomposites from the reaction mixture using an external magnet makes the present catalysts highly efficient for the reaction. Moreover, the catalyst retained its activity for five repeated runs without any drastic drop in the reactant conversion and product selectivity.